Rancang Bangun Sistem Informasi Pendaftaran Siswa Baru Berbasis Web - Rizky Fauzi; Ika Setiawan; Subarkah Abdullah (Graha Mitra Edukasi, 2026)
The New Student Admission Process (PPDB) is an essential activity in school administration aimed at recruiting prospective students. MTs Wali Songo Asy-Syirbany still conducts its new student registration process manually, starting from filling out registration forms, recording data, and storing documents. This process creates various challenges, including the risk of data loss, recording errors, delays in information processing, and inefficiencies for prospective students who must visit the school in person to register. This study aims to design and develop a web-based New Student Registration Information System for MTs Wali Songo Asy-Syirbany to improve the effectiveness and efficiency of the registration process. The system development method used is the Prototype method because it enables direct interaction and feedback from users throughout the system development process. The system was designed using the Unified Modeling Language (UML), Entity-Relationship Diagram (ERD), and Logical Record Structure (LRS). The website-based implementation includes features such as account registration, login, registration form completion, document upload, registration verification, payment verification, applicant data management, and report generation. The results of the study indicate that the developed system can automate the PPDB process, making it easier for prospective students to register online without visiting the school. In addition, the system assists the school in managing applicant data more structured, accurate, and secure, while accelerating verification and report generation. Therefore, the web-based New Student Registration Information System at MTs Wali Songo Asy-Syirbany can serve as an effective solution for improving the quality of administrative services in the new student admission process